Psychological Barriers in the Teacher’s Activity in the Implementation of the FSES - Elena Domyreva (ARPHA Proceedings, 2019)
The relevance of the issue under study is determined by the need to improve the quality of the educational process and the lack of research into the problem of psychological difficulties in the professional activity of the modern teacher. The purpose of the article is to analyze the peculiarities of psychological barriers teachers struggle with while implementing the Federal state educational standards (further - FSES). The research method was the method of questionnaire conducted among 220 teachers (divided into five groups according to the seniority – from 2 to 30 years’ work experience). The article reveals the teachers’ psychological barriers which are typical to modern education, the relationship between the types of difficulties and the strategies for coping with them. The materials presented in the article allow us to assess the current situation in the development of Russian education from the teachers’ point of view and identify psychological difficulties which must be taken into account when training and retraining professional staff.